OPTIMALISASI PEMBERDAYAAN UMKM TAS KULIT DI TANGGULANGIN BERBASIS DIGITAL MARKETING - Anisatul Septian Ika Candra; Hasan Ismail (Jurnal Ilmu Administrasi Negara, 2023)
There was a problem that arose during the time of Covid-19. Not only in terms of health but also influential in terms of economic stability. Without MSMEs is one of the activity efforts in encouraging economic development. Opportunities for MSMEs to survive during the pandemic include efforts to maximize sales on the online marketplace. The rapid development of technology or the digital world will certainly have an impact on the global economy. The purpose of this research is to help optimize the empowerment of digital marketing-based MSMEs. In this study using a qualitative descriptive method by conducting research based on the findings of the literature. And the results of the study show that small-scale commercialization must be able to compete with the MSME commercialization model that switches from offline to online. This means that digital marketing has changed the way MSMEs work from conventional systems to digital marketing-based systems with the aim of making business operations more efficient. Internet business marketing is something that is considered absolute in the global world, namely marketing through websites or social media because apart from being easy to use, effective, it is also relatively inexpensive.